EFFORTS TO PROVIDE MENTAL HEALTH SUPPORT TO CHILDREN SO THAT THEIR SOULS ARE HEALTHY - Restianingsih Putri Rahayu; Bahriyah, Fitriyani (Adisam Publisher, 2024)
When a person's physical, intellectual, and emotional growth aligns with the realization of harmony and adjustment between people, themselves, and their environment, they are said to be in good mental health. It's crucial to support kids' mental health in addition to their physical health. Both must go hand in hand without needing to focus on one point. That way, children can grow into individuals who don't get sick easily and are also mentally strong. To provide mental health support to children so that their souls are healthy, there are several steps that can be taken, namely by inviting children to talk about their feelings. Encourage children to maintain emotional and physical balance by encouraging them to engage in healthy activities, such as arranging study schedules, playing and communicating well. By taking these steps, parents can help their children maintain their mental health and build a strong foundation for their future emotional well-being. Library research techniques are used in this study. The definition and components of mental health, strategies for preserving children's mental health, and the part parents play in enhancing their mental health are all covered in this study.